Breath holding spells: Should I be worried? - Jamani, Nurjasmine Aida (The Malaysian Medical Gazette Editorial Board, Ministry Of Health Malaysia, 2018)
Adam, aged 2, was playing with his new ball. He suddenly tripped while playing and bumped his head on the ground. He got up and started to cry out loud in pain. His mother quickly came and tried to console him. Out of the sudden, he stopped breathing, his face turned blue for a couple of seconds and he passed out. About 1 minute later, his face turned pink and he was breathing again.